Towards a new (mapping of the) city: Interactive, data rich modes of urban legibility. - Wessel, Ginette.; Chang, Remco.; Sauda, Eric. (Tufts University. Tisch Library., 2017)
The modern metropolis is a vast environment replete with physical elements and complex overlays of information. The city historically has been represented as a discrete physical object, this allocentric view has become less and less useful as a method of meaningfully orientation and navigation. Today, the city is defined by technologies and flows of information that constantly change our perceptions. While it has always been true that symbolic and religious dimensions have had a place in our understanding of the city, the complex and transitory nature of the contemporary city requires a representation that is interactive rather than static. This paper presents proposals for new interactive modes of urban legibility: data space, based on the work of Bill Mitchell and Robert Venturi, virtual and physical city, established from the work of Christine Boyer and Bill Mitchell, multi-nodal, derived from the work of Tarik Fathy and Thomas Sieverts, and information flows, founded on the work of Melvin Webber. Each approach is introduced with a conceptual overview, nascent examples and a schematic proposal for a computer based urban visualization. Based on this study, we conclude that two necessary aspects of any urban visualization are interactivity and the combination of data and geospatial information. Interactivity is necessary because of the fluid nature of our experience and the diversity of individual intentions in the contemporary city. The combination of data and geospatial information is necessary because the geometry of the city had become less important as a reliable indicator of meaning.